Extracting isovolumes from three-dimensional torso geometry using PROLOG. - Replogle, J.A.
Three-dimensional (3D) finite element torso models are widely used to simulate defibrillation field quantities, such as potential, gradient and current density. These quantities are computed at spatial nodes that comprise the torso model. These spatial nodes typically number between 10 5 and 10 6, which makes the comprehension of torso defibrillation simulation output difficult. Therefore, the objective of this study is to rapidly prototype software to extract a subset of the geometric model of the torso for visualization in which the nodal information associated with the geometry of the model meets a specified threshold value (e.g., minimum gradient). The data extraction software is implemented in PROLOG, which is used to correlate the coordinate, structural and nodal data of the torso model. A PROLOG-based environment has been developed and is used to rapidly design and test new methods for sorting, collecting and optimizing data extractions from defibrillation simulations in a human torso model for subsequent visualization.
Keywords: 3D finite element torso models; PROLOG; Current density; Data extraction software; Data visualization; Defibrillation field quantities; Geometric model; Gradient; Isovolume extraction; Potential; Rapid prototyping; Sorting; Spatial nodes; Three dimensional torso geometry; Threshold value; Torso defibrillation simulation